Análisis integral de los riesgos ergonómicos y psicosociales en el contexto educativo - Ruiz Sánchez, Clara Isabe (2024)
This book comprehensively addresses the ergonomic and psychosocial risks present in the field of teaching, a sector in which the health and well-being of educators and students are crucial for academic and personal success. Through a comprehensive approach, the different dimensions of these risks are analyzed, including physical factors such as improper postures and non- ergonomic equipment, as well as psychosocial aspects such as stress, mental workload and work environment. The text not only identifies and describes the most common risks, but also offers practical strategies and recommendations to mitigate them, promoting a safer and healthier educational environment. This analysis is essential for managers, teachers, support staff and all those involved in the education sector, as it provides key tools to improve working conditions and ensure an optimal teaching-learning process.